HLA-G expression associates with immune evasion muscle-invasive urothelial cancer and drives prognostic relevance - Branz, Annalena; Matek, Christian; Lange, Fabienne; Bahlinger, Veronika; Klümper, Niklas; Hölzel, Michael; Strissel, Pamela L.; Strick, Reiner; Sikic, Danijel; Wach, Sven; Taubert, Helge; Wullich, Bernd; et al. (Frontiers in Immunology, 2024)
Urothelial bladder cancer is frequent and exhibits diverse prognoses influenced by molecular subtypes, urothelial subtype histology, and immune microenvironments. We studied the protein expression of Human Leucocyte Antigen G (HLA-G) in 241 Muscle-Invasive Bladder Cancer (MIBC) patients, elucidating its potential clinical and biological significance. HLA-G, known for immune regulation, displays significant membranous expression in tumor tissues. High HLA-G expression associates with poor overall survival (OS) and disease-specific survival (DSS), independent of clinicopathological parameters. HLA-G expression varies among molecular subtypes and Urothelial Subtype Histology, e.g., elevated expression levels in basal/ squamous MIBC and those with sarcomatoid differentiation. Notably, HLA-G is increased in MIBC with an immune evasive microenvironment (high PD-L1 tumor cell expression, NK cell depletion, granzyme B (GZMB)/CD8 ratio reduction, MHC class I (MHCI) expression reduction) that are characterized by immunosuppressive features and poor prognosis. Furthermore, HLA-G correlates with elevated levels of other immune checkpoint proteins (TIGIT, LAG3, CTLA-4), indicating its role in immune evasion. Our findings underscore HLA-G's role as a potential prognostic marker and interesting immunotherapeutic target in MIBC. Its impact on immune evasion mechanisms and broad expression, coupled with associations with poor survival and distinct tumor phenotypes, positions HLA-G as a promising protein for further exploration in developing targeted immunotherapies for MIBC patients.